2023
DOI: 10.1002/cpt.2974
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Polyglutamates Exposure – Response Modeling in a Large Cohort of Rheumatoid Arthritis Patients Starting Methotrexate

Abstract: Methotrexate polyglutamates (MTX‐PG) concentrations in red blood cells (RBCs) have been suggested as a biomarker of response in patients with rheumatoid arthritis (RA) receiving low‐dose MTX therapy. We investigated the association and interpatient variability between RBC‐MTX‐PG3‐5‐exposure and response in patients with RA starting MTX. Data of three prospective cohorts were available. The relationship between exposure and Disease Activity Score in 28 joints (DAS28) was analyzed using a population pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…>50 nmol/L for MTX‐PG 3 at 3 months treatment) matched those previously observed in other IMIDs 3 (>60 nmol/L MTX‐PG 3 5 , >74 nmol/L MTX‐PG total 6 , >83 nmol/L MTX‐PG total 7 . Combination of our three prospective RA cohorts in a PKPD modelling study, revealed an effective concentration range of 47–78 nmol/L MTX‐PG 345 at 3 months of therapy 4 . Thus, the PKPD prerequisites for applying TDM have been met.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…>50 nmol/L for MTX‐PG 3 at 3 months treatment) matched those previously observed in other IMIDs 3 (>60 nmol/L MTX‐PG 3 5 , >74 nmol/L MTX‐PG total 6 , >83 nmol/L MTX‐PG total 7 . Combination of our three prospective RA cohorts in a PKPD modelling study, revealed an effective concentration range of 47–78 nmol/L MTX‐PG 345 at 3 months of therapy 4 . Thus, the PKPD prerequisites for applying TDM have been met.…”
supporting
confidence: 84%
“…Our study identified MTX‐PG 3 as the most suitable parameter for therapeutic drug monitoring (TDM). MTX‐PG 345 emerged as a viable alternative, based on its correlation with biochemical response in our cohort and the results of a recent pharmakinetic/pharmacodynamic (PKPD) modelling study in RA 4 . The next step is to establish a therapeutic range or threshold.…”
mentioning
confidence: 99%